Research data sharing: what the FRIC? - Phillips, Brenda; Proudfoot, Rachel E. (My University, 2016)
Poster presented by Brenda Phillips and Rachel Proudfoot (both of Research Data Leeds at the University of Leeds) at RepoFringe 2016. The poster subtitle reads: "Lots of cooperation is needed to help researchers share data safely and make sure institutions have a consistent and coherent approach to data management. Here are some of the key players and policies..."
Keywords: Data sharing; Research Data Management